2013
DOI: 10.1002/aic.14037
|View full text |Cite
|
Sign up to set email alerts
|

Probability distributions of gas hydrate formation

Abstract: in Wiley Online Library (wileyonlinelibrary.com) Induction time distributions for gas hydrate formation were measured for gas mixtures of methane 1 propane at pressures up to 11.3 MPa using a high-pressure automated lag time apparatus (HP-ALTA). Measurements were made at subcooling temperatures between 4.3 and 13.5 K and, while isothermal induction times between 0 and 15,000 s were observed, the median isothermal induction times for the distributions ranged from 100 to 4000 s. A hyperbolic relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 18 publications
1
41
1
Order By: Relevance
“…At all concentrations, it was observed that the hydrate formation temperature increased with operating pressure as shown in Figure (20), these results perfectly agreed with the published literature (Moraveji et al, 2010;Wu et al, 2013).…”
Section: Pressure Effect On Formation Temperature Point For Dpcsupporting
confidence: 90%
“…At all concentrations, it was observed that the hydrate formation temperature increased with operating pressure as shown in Figure (20), these results perfectly agreed with the published literature (Moraveji et al, 2010;Wu et al, 2013).…”
Section: Pressure Effect On Formation Temperature Point For Dpcsupporting
confidence: 90%
“…Results of hydrate nucleation induction time vs. wax contents and stirring rates under the initial pressure of 7.0 MPa are shown in Figure . Although the number of trials conducted by this high‐pressure hydrate slurry rheological measurement system does not reach a statistically significant number, the inhibition influence of wax crystals on hydrate nucleation induction time is clearly defined. To analyze the influence of wax content on hydrate nucleation induction time more clearly, a wax content influence factor (WI) is defined as Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows schematically the first-generation high-pressure automated lag time apparatus (HP-ALTA MkI) used in this study. Both the instrumental capabilities and modes of operation of HP-ALTA MkI can be found in refs . An HP-ALTA can apply a large number of linear (constant cooling rate) cooling ramps to a small quiescent water sample of well-defined dimensions under isobaric conditions, detect the formation of gas hydrate on the surface of the sample water, and record the temperature at which the hydrate formation occurred.…”
Section: Methodsmentioning
confidence: 99%